THE CONSTITUTIONAL BASIS FOR ENSURING THE MIRANDA RULE IN CRIMINAL PROCEEDINGS - Mirzayev, Sh.; Xodjayev, SH.; Zokirov, SH. (Educational Research in Universal Sciences, 2023)
This article analyzes the views on the “Miranda rule” included in the new version of the Constitution of the Republic of Uzbekistan regarding human rights. The experience of some foreign countries on the “Miranda rule” was presented. The essence of the reflection of this provision in the Constitution was explained.